ACTIVITY OF DAILY LIVING DAN KUALITAS HIDUP PASIEN PASCA STROKE ISKEMIK - Mather, Mather; Rahayu, Rahayu; Amandus, H; Sudarto, Sudarto; Triyani, Irma (Jurnal Keperawatan dan Kesehatan, 2024)
Ischemic stroke, also referred to as non-hemorrhagic stroke, results in the death of brain tissue due to impaired blood flow, primarily caused by blockages in the cerebral or cervical arteries and, less commonly, in the cerebral veins. This condition profoundly affects various aspects of an individual's life, including physical, emotional, psychological, cognitive, and social well-being. Following a stroke, many individuals experience reduced independence and mobility, which significantly detracts from their quality of life. Often, they face self-care deficits and require assistance to gradually regain the ability to perform activities of daily living (ADL) independently. This study aims to elucidate the strong relationship between ADL independence and the quality of life of post-ischemic stroke patients at Abdul Aziz Hospital in Singkawang City. Employing an analytic observational design with a cross-sectional approach, the research involved a sample of 60 respondents selected from the Neurology Polyclinic at RSUD dr. Abdul Aziz through purposive sampling. Data analysis was conducted using the Spearman Rank test with a 95% confidence level. The results indicate a significant relationship between ADL independence and the quality of life of these patients, as demonstrated by a p-value of 0.000 (p < α) and a correlation strength of 0.514, categorized as moderate (0.40 – 0.599). These findings highlight that the level of independence in activities of daily living is intrinsically linked to the quality of life for post-ischemic stroke patients.